2021
DOI: 10.3389/fmolb.2021.706949
|View full text |Cite
|
Sign up to set email alerts
|

CD74 Correlated With Malignancies and Immune Microenvironment in Gliomas

Abstract: Background: Cluster of differentiation 74 (CD74) is found to be highly involved in the development of various types of cancers and could affect the activities of infiltrated cells in the tumor microenvironment. However, these studies only focus on a few types of immune cells. Our study aims to comprehensively explore the role of CD74 in glioma prognosis and immune microenvironment.Methods: A total of 40 glioma specimens were collected in this study. We extracted data from The Cancer Genome Atlas (TCGA), Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
(58 reference statements)
1
18
0
Order By: Relevance
“…also involved in glioma immune infiltration, is closely associated with the existence of multiple immune cells(Xu et al, 2021). Our study also confirmed a correlation between CD74 and various immune cells and functions.…”
supporting
confidence: 85%
“…also involved in glioma immune infiltration, is closely associated with the existence of multiple immune cells(Xu et al, 2021). Our study also confirmed a correlation between CD74 and various immune cells and functions.…”
supporting
confidence: 85%
“…found that ALKBH5 promoted the generation of immunosuppressive tumor microenvironment via hypoxia-induced paraspeckle assembly and IL8 secretion ( 73 ). These results suggested that ALKBH5 could be acted as a potential therapeutic target for glioma and as a novel marker to predict prognosis of glioma patients ( 74 ). In addition, analysis of the seven inflammation and immune related clusters suggested that high ALKBH5 expression activated the antigen-presenting cells and lymphocytes, and enhanced interferon signaling in the glioma tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Some of them have already been reported. For instance, the roles of PROS1-AXL (34), LAT-TNFRSF1B (35), ANXA1-FPR1 (36,37), MIF-CD74 (38)(39)(40), SPP1-CD44 (41), VEGFB-VEGFR (42), IL6-IL6R (43), and OSM-OSMR (44) have been confirmed in macrophage activation in GBM. Additionally, more novel combinations are first proposed in this work, including TRAIL signaling pathway (TNFSF10-TNFRSF10B), TWEAK signaling pathway (TNFSF12-TNFRSF12A), VISFATIN signaling pathway (NAMPT-(ITGA5+OTGB1)), ncWNT signaling pathway (WNTSA-FZD3), PARs signaling pathway (PRSS3-F2R), and RESISTIN signaling pathway (RETN-CAP1).…”
Section: Discussionmentioning
confidence: 99%